The Teacher’s Responsibility (Eurasian Research Bulletin, 2022)
The ultimate purpose of assessment for learning is to create self-regulated learners who can leave school able and confident to continue learning throughout their lives. Teachers need to know at the outset of a unit of study where their students are in terms of their learning and then continually check on how they are progressing through strengthening the feedback they get from their learners. Students are guided on what they are expected to learn and what quality work looks like. The teacher will work with the student to understand and identify any gaps or misconceptions (initial/diagnostic assessment).